Indeks Ketahanan Sosial Rumah Tangga Nelayan Skala Kecil (Studi Kasus di Teluk Prigi Kabupaten Trenggalek) - Purwanti, Pudji; Intyas, Candra Adi; Sofiati, Dwi; Fattah, Mochammad (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2024)
Small-scale fishermen dominate the number of fishermen in Prigi Bay. Some basic non-food household expenditure variables can be used to measure the social resilience index of fisher households. This study analyses the social resilience index of small-scale fisher households based on 4 criteria: Health, Education, Social capital and housing. The number of respondents used in this study was 75 fishermen. The results showed that the value of the health dimension of small-scale fisher households of each indicator was dominated by the highest score. The education dimension is good as shown by the highest score, but there is also a low score for reading parks and non-formal education. The social capital dimension is quite good, but there are low scores for unpaid public facilities, no sports groups and no access to special schools. While the settlement dimension has high scores for all indicators. The total social resilience score of health, education, social capital and settlements is 133. This means the Social Resilience index value based on the 4 criteria above is 70%. This value is included in the category of vulnerability resistance.